Effect of densification pretreatment on combustion and particulate matter emission characteristics of agricultural biomass - Wei Yang; Shilong Feng; Yongming Xu; Youjian Zhu; Shanzhi Xin; Wenbo Hu; Heyong Li; Pan Li; Huihui Liu; Haiping Yang (Royal Society Open Science)
Agricultural biomass production in China is substantial, and the densification pretreatment of agricultural biomass has the potential to reduce usage costs and increase fuel energy density. However, there is still uncertainty regarding the impact of densification pretreatment on combustion characteristics and particulate matter emissions. In this study, the combustion characteristics of raw biomass and biomass pellets were investigated using a thermogravimetric analyser and fixed-bed reactor with cotton stalk and rice husk. The findings indicate that biomass densification pretreatment enhances combustion performance, resulting in more concentrated and intense combustion compared with untreated biomass. The combustion models become more intricate due to the process of densification pretreatment. For cotton stalk, densification pretreatment proves beneficial in reducing the emission of PM0.1–10 (particulate matter with a diameter between 0.1 and 10 µm), although it does not exhibit a discernible inhibitory effect on ultrafine particles (<0.1 μm). Densification pretreatment has also been shown to suppress the conversion of alkali metal sulfides into particulate matter. In the case of rice husk, densification pretreatment primarily reduces PM1–10 emissions while simultaneously increasing the formation of fine particles (<1 μm). This process facilitates the interaction between Si and alkali metal chlorides, thereby enhancing silicate reaction and impeding the conversion of alkali metal chlorides into PM1. However, the impact of densification pretreatment on the elemental composition of PM1–10 remains insignificant in both biomass samples.